Rancang Bangun Sistem Top-Up Meteran PDAM Berbasis Mikrokontroller - Indar Kusmanto; Yuyun; Andani Achmad (Bulletin of Information Technology (BIT), 2022)
This research aims to build a top-up based PDAM meter tools, which allows users to control water use in their daily needs. This type of research is experimental research where the scope of the problem can be carried out using the literature study method, field data collection methods. The system is made in the form of a prototype. This research produces a product in the form of a tool with a top-up as a payment system. This study uses an RFID sensor as a tool to enter voucher balances into the system. Then arduino uno as a controller of water use through a waterflow sensor and a solenoid valve instead of a faucet to close the water flow. The result of this research is that the device can display information in the form of remaining voucher balances and the amount of water consumption. In this study, water measurement trials have been carried out with an error value of 2.53 percent, and trial charging vouchers worth 20,000 to 100,000, as well as trial use and remaining balance with appropriate results